An empirical study of GUI widget detection for industrial mobile games - YE, Jiaming (Institutional Knowledge at Singapore Management University, 2021)
With the widespread adoption of smartphones in our daily life, mobile games experienced increasing demand over the past years. Meanwhile, the quality of mobile games has been continuously drawing more and more attention, which can greatly affect the player experience. For better quality assurance, general-purpose testing has been extensively studied for mobile apps. However, due to the unique characteristic of mobile games, existing mobile testing techniques may not be directly suitable and applicable. To better understand the challenges in mobile game testing, in this paper, we first initiate an early step to conduct an empirical study towards understanding the challenges and pain points of mobile game testing process at our industrial partner NetEase Games. Specifically, we first conduct a survey from the mobile test development team at NetEase Games via both scrum interviews and questionnaires. We found that accurate and effective GUI widget detection for mobile games could be the pillar to boost the automation of mobile game testing and other downstream analysis tasks in practice. We then continue to perform comparative studies to investigate the effectiveness of state-of-the-art general-purpose mobile app GUI widget detection methods in the context of mobile games. To this end, we also develop a technique to automatically collect GUI widgets region information of industrial mobile games, which is equipped with a heuristic-based data cleaning method for quality refinement of the labeling results. Our evaluation shows that: (1) Existing GUI widget detection methods for general-purpose mobile apps cannot perform well on industrial mobile games. (2) Mobile game exhibits obvious difference from other general-purpose mobile apps in the perspective GUI widgets. Our further in-depth analysis reveals high diversity and density characteristics of mobile game GUI widgets could be the major reasons that post the challenges for existing methods, which calls for new research methods and better industry practices. To enable further research along this line, we construct the very first GUI widget detection benchmark, specially designed for mobile games, incorporating both our collected dataset and the state-of-the-art widget detection methods for mobile apps, which could also be the basis for further study of many downstream quality assurance tasks (e.g., testing and analysis) for mobile games.